Fire fighting pumping systems at industrial facilities - Nolan, Dennis P. (Academic Press ; Gulf Professional, 2011)
Written from the perspective of industrial users, this is the only book that describes how to install an effective firewater pumping system in a pragmatic and budget-conscious way rather than with purely the regulatory framework in mind. Based on the wide-ranging industrial experience of the author, this book is also the only one that deals with the particular risks and requirements of off-shore facilities. This book takes the reader beyond the prescriptive requirements of the fire code (NFPA, UL) and considers how to make the best choice of design for the budget available.
Keywords: Industrial buildings -- Fires and fire prevention -- Equipment and supplies.; Fire pumps.; Industries.; elektronické knihy; electronic books